Effect of Cu content on microstructure and high-temperature oxidation behaviors of AlCuxCoCrFeNi2.1 high-entropy alloys manufactured by laser directed energy deposition - Zhaoyang Liu; Jiawei Liu; Xiaokang Fan; Tao Zou; Zhongwei Liang (Journal of Materials Research and Technology)
In this study, thin-wall builds of AlCuxCoCrFeNi2.1 (x = 0.00, 0.25, 0.50, 0.75, 1.00, 1.25) high-entropy alloys were additively manufactured by laser direct energy deposition process. The effect of Cu content on microstructure evolution and high-temperature oxidation behaviors of prepared HEAs was studied. The results showed that the increase of Cu content facilitates the microstructure transformation from fine FCC/BCC lamellar eutectic structure to well-developed FCC columnar dendrites and depleted BCC interdendrites. Drastic Cu segregation mainly is formed at the outside edges of FCC columnar dendrites. During the high-temperature oxidation process, the sample with x = 0.00 generates relative complete oxide layer predominantly composed of Cr2O3 upper-layer and Al2O3 inner-layer. Plenty of AlN particles are formed beneath the oxidized surface of matrix. In the samples with x = 0.25 to 1.25, the added Cu brings in numerous nanoscale Cu2O particles within the oxide layer, which not only preferentially thickens the oxide layer by promoting the formation of Al2O3, but also causes numerous microscale voids by inhabiting and further decomposing the AlN particles. Due to the serious coefficient of thermal expansion difference between copper oxides, oxide layer and matrix, the Cu-rich outline edges of columnar dendrites contribute to the formation of humped stripes at oxidized surface and promote the initial cracking of oxide layer. The increase of Cu content facilitates the cracking and spalling of oxide layer by deteriorating the adhesion force between oxide layer and matrix, and resultantly exacerbates high-temperature oxidation resistance of the AlCuxCoCrFeNi2.1 HEAs.